Silent Screens: Evaluating the Visibility of Maternal Mental Health in Kerala’s WCD Social Media Platforms - Jacob, Ann; Babu, S. Dinesh (Journal of Neonatal Surgery, 2025)
This study investigates the portrayal of maternal mental health, particularly postpartum depression, in the digital communication initiatives of the Kerala Women and Child Development Department between 2020 and 2024. Employing a qualitative thematic analysis approach, the research examines the frequency, framing, and prominence of maternal mental health content across 2,036 posts and videos on three major social media platforms: Instagram, Facebook, and YouTube, in relation to other health and welfare themes. The results indicate a significant underrepresentation of maternal mental health, with only 8 posts directly addressing postpartum depression. Conversely, topics like parenting, nutrition, and women's protection were extensively featured. The analysis reveals a thematic imbalance, wherein the emotional and psychological challenges of motherhood are either absent or minimally integrated into the broader digital health discourse. Furthermore, the communication strategy was dominated by symbolic and ceremonial content, including celebration posts and celebrity endorsements, which further marginalized substantive mental health messaging. The findings indicate a substantial institutional gap in addressing maternal psychological well-being, despite its policy-level recognition. This paper advocates for the integration of consistent, expert-driven, and empathetic maternal mental health communication within Kerala's digital public health outreach. Recommendations encompass launching dedicated maternal mental health campaigns, enhancing the visibility of support services, and rebalancing thematic priorities to ensure that mental health is treated as an integral component of maternal care